Fenomena Waithood di Indonesia: Sebuah Studi Integrasi antara Nilai-Nilai Keislaman dan Sosial Kemanusiaan - Andika Andika; Ahmad Yani; Eka Mulyo Yunus; Muria Khusnun Nisa; Abdul Halim; Mufdil Tuhri (Jurnal Riset Agama, 2021)
This study aims to understand the waithood phenomenon in Indonesia caused by changes in people's behavior in social life, by integrating Islamic and social human values. This study uses a qualitative approach through descriptive-analytical methods. The results and discussion of this study show an effort to understand the waithood phenomenon by integrating Islamic and social humanitarian perspectives. This study concludes that understanding the waithood p henomenon can be integrated with Islamic and social humanitarian perspectives. This study recommends social figures and communities in understanding the waithood phenomenon.